KINETICS OF HARDENING OF EPOXY-AMINE SYSTEMS DOPED WITH LiClO4 - Demchenko, Valeriy; Matkovska, Liubov; Matkovska, Оlga (V.I.Vernadsky Institute of General and Inorganic Chemistry, 2022)
Kinetic methods for analyzing the curing process of thermosetting polymer systems are an important area for controlling the formation conditions for viscosity, which depends on the temperature and chemical composition of the composite. The curing reactions determine the morphology and structure of the system, affecting the properties of the final material. This work analyzes the curing process of polymer composites based on epoxy oligomer - polyethylene glycol diglycidyl ether (DEG), polyethylene polyamine hardener (PEPA) and lithium perchlorate salt LiClO4. The initial components, the mixture of DEG/PEPA composition and the DEG/PEPA/LiClO4 system supplemented with salt were investigated. Using the methods of Fourier-transform infrared spectroscopy and rheological analysis in dynamic mode the curing conditions of the systems were established. It was shown that the nature of the distribution of vibration bands in the IR spectra of the DEG/PEPA and DEG/PEPA/LiClO4 systems is a superposition of the IR spectra of the initial components. Lithium perchlorate in the salt-doped initial system is in an undissociated state and dissociates in the polymer matrix over time during the curing of the system. In particular, the time dependences of the concentration of epoxide groups in the DEG/PEPA system calculated using the integral intensity ratios were analyzed by IR spectroscopy data. To study the curing process with increased segmental mobility of the reacting macromolecules, rheokinetic measurements were performed at 50°C. Analysis of the nature of changes in the elastic and viscosity moduli over time allowed us to estimate the gel time of the initial and doped systems. Differences in the IR spectra for both systems before the formation of the three-dimensional structure and at the gel point, as well as the IR spectra of these systems after the curing reaction, were analyzed. Attention was also paid to the nature of the influence of dopant on the curing process and its state in the mixture/composite of DEG/PEPA/LiClO4 composition. Lithium perchlorate LiClO4 is an effective catalyst for the aminolysis of the oxirane ring, which explains the acceleration of the curing reaction of the system in the presence of salt.